Não-adesão à terapêutica medicamentosa em indivíduos com hipertensão arterial em Maringá - Paraná - Barreto, Mayckel da Silva (2012)
Arterial hypertension has multi-factor genesis, insidious chronic character and oligo-/asymptomatic evolution, all of which contribute to treatment non-compliance, resulting in inadequate blood pressure control. For its part, maintaining high tension levels represents a risk factor for the onset of medium- to long-term complications. Therefore nurses, as key elements in the process of assisting hypertensive persons should learn and acknowledge their characteristics, potentials, difficulties and true needs, so that from those, they can devise and implement intervention strategies that favor treatment compliance and blood pressure control. With that, the main objective of the study was to identify the prevalence of non-compliance to drug treatment in the city of Maringá (PR) and assess the association of socioeconomic, assistance and personal factors with non-compliance with drug treatment, inadequate blood pressure control and hospitalization of individuals with hypertension monitored by primary care, and also understand how individuals with hypertension perceive the influence of family on treatment compliance/non-compliance. The study had two different methodological dimensions: one quantitative, descriptive and cross-sectional performed with 422 hypertensive individuals; and another, qualitative and descriptive, performed with 18 subjects with hypertension. Data were collected during the months of December 2011 and March 2012, through home visits using a semi-structured questionnaire. The results showed that most interview subjects were female (59.48%), married (68.96%), elderly (63.25%), with low family income (82.94%), with other co-morbidities (61.14%), low educational level (63.51%) and recent diagnosis (56.16%). According to the instrument used, 180 individuals (42.65%) were regarded as non-compliant with drug treatment; those with little knowledge about the illness, complex drug treatment and dissatisfaction with health services had the highest likelihood of not complying with therapy. Another important finding was that more than half of all interviewed subjects (44.89%) showed inadequate blood pressure control, which was significantly associated with older age, non-compliance with drug treatment, non-attendance of scheduled appointments and three or more anti-hypertensive drug prescriptions. The prevalence of hospitalization from complications of the illness was small (12.08%) and in most cases occurred due to a hypertensive or pseudo-hypertensive crisis (47.05%), with the greatest likelihood of being hospitalized coming from males, elderlies, those non-compliant with drug treatment, with inadequate blood pressure control and comorbidities. The analysis of qualitative data evidenced that the family was described as a facilitator of treatment compliance and motivator of selfcare practices, and when this situation did not occur, it was because the individuals felt responsible for controlling their own illness; however, some participants reported not receiving family support at the desired level. All of these findings reinforce the need for primary care nurses to work to develop closer bonds with hypertensive individuals and their families, as well simplify the therapeutic protocols and perform more health promotion activities, relaying information and raising awareness among the hypertensive population regarding the harm caused by non-compliance to treatment.